A tissue filling composition and its preparation method and application
By using a composition of crosslinked dextran microspheres and polyelectrolyte gel, the problem of cumbersome and unstable treatment steps of crosslinked sodium hyaluronate gel in the prior art is solved, and the stability and excellent performance of the tissue filling composition are achieved.
Patent Information
- Application Number
- CN202510008373.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-08
AI Technical Summary
The dialysis removal steps of crosslinked sodium hyaluronate gels in the prior art are cumbersome and time-consuming, and the gel may undergo swelling and degradation during the dialysis process, resulting in structural instability.
The tissue-filled composition with stability and excellent properties is prepared by a composition of crosslinked dextran microspheres and polyelectrolyte gel by specific preparation methods, including dissolution, emulsification and crosslinking of dextran in aqueous sodium hydroxide solution.
The preparation process is simplified, the stability and swelling rate of polyelectrolyte gel are improved, the degradation cycle of crosslinked dextran microspheres is extended, and the continuous stimulation of collagen regeneration and excellent injectability are achieved.
Smart Images

Figure CN119770737A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomaterials, and in particular to a tissue filling composition and a preparation method and application thereof. Background Art
[0002] Dextran, also known as dextran, is a polymer formed by D-glucose molecules linked by α-1-6 glycosidic bonds. Cross-linked dextran microspheres are tiny polymer spheres generated by a chemical reaction between dextran and a cross-linking agent. Dextran has excellent biocompatibility, high stability, easy degradation in the body, and can effectively promote collagen regeneration. In view of these advantages, in recent years, cross-linked dextran gel has been increasingly used in clinical practice as an emerging type of tissue filling material.
[0003] Chinese patent CN108721206A discloses a composition for treating vesicoureteral reflux, urinary incontinence and fecal incontinence and its preparation method, wherein cross-linked sodium hyaluronate gel is used as a dispersion medium and carrier of the composition to deliver cross-linked dextran microspheres to the injection site. Among them, cross-linked sodium hyaluronate dry powder is a cross-linked sodium hyaluronate gel prepared in advance by the method disclosed in patent CN103923328A. The preparation process of cross-linked sodium hyaluronate disclosed in the patent has complicated steps, and the preparation process requires the use of more reagents such as acetone, dimethyl sulfoxide, ethanol, as well as vacuum drying, homogenization treatment, etc., to obtain a cross-linked sodium hyaluronate gel with stable low pushing force of different particle sizes.
[0004] In current technology, the dialysis impurity removal step used to process cross-linked sodium hyaluronate gel is cumbersome and time-consuming. This process requires the use of chemical reagents such as acids and alkalis to adjust the pH of the gel. What is more complicated is that the gel may undergo swelling and degradation during dialysis, resulting in instability of the gel structure. Summary of the invention
[0005] In order to solve the problems in the prior art, the present invention provides a tissue filling composition. The preparation raw materials include 4-6% cross-linked dextran microspheres, 1-2% polyelectrolyte gel, and water to make up the balance, calculated by mass percentage; the pH value of the tissue filling composition is 6-8, and the swelling rate is -50% to 50%.
[0006] In one embodiment, the method for preparing the cross-linked dextran microspheres comprises the following steps:
[0007] S1. Dissolve dextran in a sodium hydroxide aqueous solution to obtain an aqueous phase, premix 1,4-butanediol diglycidyl ether with the aqueous phase, control the premixing temperature at 10-25° C., and control the rotation speed at 100-600 rpm to obtain solution A;
[0008] S2, dissolving Span 80 in liquid paraffin to obtain an oil phase, and transferring the oil phase to a device with stirring and temperature control functions;
[0009] S3, adding the solution A to the oil phase for emulsification reaction, wherein the temperature of the emulsification reaction process is 20-80° C., the rotation speed is controlled at 100-800 rpm, and the emulsification time is 0.1-2 h; after the reaction, adding 1,4-butanediol diglycidyl ether for cross-linking reaction, wherein the temperature of the cross-linking process is 20-80° C., the rotation speed is 100-800 rpm, and the cross-linking time is 4-50 h;
[0010] S4. After the reaction in step S3 is completed, solid-liquid separation, impurity removal, sieving, and vacuum freeze-drying are performed to obtain the product.
[0011] In one embodiment, the concentration of the dextran in the aqueous phase is 0.4-0.5 g / mL.
[0012] In one embodiment, the concentration of the sodium hydroxide aqueous solution is 0.2-1 mol / L.
[0013] In one embodiment, the concentration of Siban 80 is 0.04-0.08 g / g.
[0014] In one embodiment, in step S3, the mass ratio of 1,4-butanediol diglycidyl ether to dextran is (0-1):1.
[0015] In one embodiment, the solid-liquid separation in the S4 step is specifically as follows: the solution after the reaction in the S3 step is transferred to a clean container, cooled and allowed to stand for 10 to 30 minutes, the upper liquid is removed, and a 50% ethanol aqueous solution containing 1 to 5% Tween 80 is added to the remaining reaction material, stirred at a stirring speed of 400 to 800 rpm for 30 to 60 minutes, allowed to stand for 10 to 30 minutes, and solid-liquid separation is performed to obtain microspheres.
[0016] In a preferred embodiment, the volume ratio of the 50% ethanol aqueous solution containing 1-5% Tween 80 to the remaining reaction materials is (3-10):1.
[0017] In one embodiment, the impurity removal in the S4 step is specifically as follows: adding 50% ethanol aqueous solution to the microspheres to completely immerse the microspheres, stirring for 30 to 60 minutes, standing for 10 to 30 minutes, solid-liquid separation, to obtain microspheres, repeating the above steps 3 times, adding purified water to the microspheres to completely immerse the microspheres, stirring for 30 to 60 minutes, standing for 10 to 30 minutes, solid-liquid separation, repeating 3 times, to obtain microspheres after impurity removal.
[0018] In one embodiment, the screening in step S4 is specifically: passing the impurity-free microspheres through a 100-350 μm sieve.
[0019] In one embodiment, the raw materials for preparing the polyelectrolyte gel include a cationic polymer, an anionic polymer and water.
[0020] In one embodiment, the method for preparing the polyelectrolyte gel comprises the following steps:
[0021] (1) preparing a cationic polymer solution: dissolving the cationic polymer in water, stirring until the cationic polymer is completely dissolved, and setting aside;
[0022] (2) preparing anionic polymer solution: dissolving anionic polymer in water, stirring until the anionic polymer is completely dissolved, and setting aside;
[0023] (3) mixing: mixing the cationic polymer solution and the anionic polymer solution and stirring until flocs are generated, which is referred to as mixture A;
[0024] (4) The mixture A is centrifuged to remove the supernatant to obtain the product.
[0025] In one embodiment, the cationic polymer comprises chitosan quaternary ammonium salt.
[0026] In one embodiment, the anionic polymer includes at least one of sodium hyaluronate and sodium carboxymethyl cellulose.
[0027] In one embodiment, the mixing and stirring time in step (3) is 5 to 30 minutes, which can be 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, or 30 minutes.
[0028] In one embodiment, the volume ratio of the cationic polymer solution to the anionic polymer solution in step (3) is (0.5-2):1, which may be 0.5:1, 1:1, 1.5:1, or 2:1.
[0029] In one embodiment, the concentration of the cationic polymer solution is 0.2 to 2 g / mL.
[0030] In a preferred embodiment, the concentration of the cationic polymer solution is any one of 0.2 g / mL, 0.3 g / mL, 0.4 g / mL, 0.5 g / mL, 0.6 g / mL, 0.7 g / mL, 0.8 g / mL, 0.9 g / mL, 1 g / mL, 1.5 g / mL, and 2 g / mL.
[0031] In one embodiment, the concentration of the anionic polymer solution is 0.2-1 g / mL.
[0032] In a preferred embodiment, the concentration of the anionic polymer solution is any one of 0.2 g / mL, 0.3 g / mL, 0.4 g / mL, 0.5 g / mL, 0.6 g / mL, 0.7 g / mL, 0.8 g / mL, 0.9 g / mL, and 1 g / mL.
[0033] In a preferred embodiment, the step (4) is specifically as follows: centrifuging the mixture A at a centrifugal force of 1000 to 10000 G for 5 to 30 minutes and removing the supernatant to obtain the mixture.
[0034] The second aspect of the present invention provides a method for preparing the above tissue filling composition, which comprises at least the following steps: adding cross-linked dextran microspheres to the polyelectrolyte gel and stirring evenly to obtain the composition.
[0035] The third aspect of the present invention provides an application of the tissue filling composition, which is applied to the preparation of biological materials for treating stress urinary incontinence.
[0036] In one embodiment, the preparation method of the biological material for treating stress urinary incontinence is as follows: the tissue filling composition is filled and sterilized by high-pressure steam to obtain the biological material.
[0037] Beneficial Effects
[0038] 1. The tissue filling composition provided by the present invention adopts a specific process to prepare a polyelectrolyte hydrogel. The process is simple and no additional chemical cross-linking agent is added. By controlling the material selection and concentration of anionic and cationic polymers, the stability, swelling rate, degradation cycle and other properties of the polyelectrolyte hydrogel are improved.
[0039] 2. The cross-linked dextran microspheres prepared by a specific process in the tissue filling composition provided by the present invention have a rounded morphology, a long degradation cycle, and can continuously stimulate collagen regeneration.
[0040] 3. The tissue filling composition provided by the present invention controls the dosage ratio of cross-linked dextran microspheres and polyelectrolyte hydrogel, so that the cross-linked dextran microspheres in the prepared tissue filler can be evenly dispersed in the polyelectrolyte hydrogel, and the tissue filler has a suitable swelling rate and excellent injectability. The cross-linked dextran microspheres will not be damaged during the injection process, and the microspheres maintain integrity. The polyelectrolyte hydrogel is used as a carrier to transport the cross-linked dextran microspheres to the injection site. As the polyelectrolyte hydrogel is absorbed by the tissue, the dextran microspheres stimulate fibroblasts to produce new collagen tissue on their periphery, and the dextran microspheres are wrapped to form collagen capsules. The collagen capsules not only have a filling effect, but also further stabilize the volume of the dextran microspheres to achieve a lasting filling effect.
[0041] 4. The tissue filling composition prepared by the method of the present invention has readily available raw materials, is easy to prepare, has low cost, and is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a test chart of the swelling rate of the polyelectrolyte gel produced in the preparation process of Example 1-5 after accelerated aging at 60° C. for 10 days.
[0043] Figure 2 This is a test diagram of the injectability of the polyelectrolyte gel produced during the preparation process of Example 1.
[0044] Figure 3 This is a graph showing the injectability test of the tissue filling composition prepared in Example 1. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the examples and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The experimental methods for which specific conditions are not specified in the examples are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be purchased commercially.
[0046] Example 1
[0047] In a first aspect, the present embodiment provides a tissue filling composition. The raw materials for preparation include 5% cross-linked dextran microspheres, 1.5% polyelectrolyte gel, and the balance is made up of water, calculated by weight percentage.
[0048] The pH value of the tissue filling composition is 6.83, and the swelling rate is 6.17%.
[0049] The preparation method of the cross-linked dextran microspheres comprises the following steps:
[0050] S1. Dissolve 40 g of dextran in 100 g of 0.5 mol / L sodium hydroxide aqueous solution to obtain an aqueous phase, premix 16 g of 1,4-butanediol diglycidyl ether with the aqueous phase for 1 h at a premixing temperature of 22° C. and a rotation speed of 300 rpm to obtain a solution A;
[0051] S2, dissolving 60g of Span 80 in 1000g of liquid paraffin to obtain an oil phase, and transferring the oil phase to a device with stirring and temperature control functions;
[0052] S3, adding the solution A to the oil phase to carry out an emulsification reaction; the temperature of the emulsification reaction process is 40°C, the rotation speed is 300rpm, and the emulsification time is 20min; after the reaction is completed, no crosslinking agent is added to the reaction system, the temperature of the crosslinking process is 40°C, the rotation speed is 300rpm, and the crosslinking time is 15h;
[0053] S4. After the reaction in step S3 is completed, solid-liquid separation, impurity removal, sieving, and vacuum freeze-drying are performed to obtain the product.
[0054] The solid-liquid separation in the step S4 is specifically as follows: the solution after the reaction in the step S3 is transferred to a clean container, cooled and allowed to stand for 10 minutes, the upper liquid is removed, 500 mL of a 50% ethanol aqueous solution containing 1-5% Tween 80 is added to the remaining reaction material, stirred at a stirring speed of 600 rpm for 30 minutes, allowed to stand for 20 minutes, and solid-liquid separation is performed to obtain microspheres.
[0055] The impurity removal in step S4 is specifically as follows: adding 500 mL of 50% ethanol aqueous solution to the microspheres to completely immerse the microspheres, stirring for 30 min, standing for 10 min, and solid-liquid separation to obtain microspheres, repeating the above steps 3 times, adding 500 mL of purified water to the microspheres to completely immerse the microspheres, stirring for 30 min, standing for 10 min, and solid-liquid separation, repeating 3 times to obtain microspheres after impurity removal.
[0056] The screening in step S4 specifically includes: passing the impurity-removed microspheres through a 100-350 μm sieve.
[0057] The raw materials for preparing the polyelectrolyte gel include cationic polymer, anionic polymer and water.
[0058] The preparation method of the polyelectrolyte gel comprises the following steps:
[0059] (1) preparing a cationic polymer solution: dissolving chitosan quaternary ammonium salt in water, stirring until the chitosan quaternary ammonium salt is completely dissolved, and setting aside;
[0060] (2) preparing anionic polymer solution: dissolving sodium hyaluronate in water, stirring until the sodium hyaluronate is completely dissolved, and setting aside;
[0061] (3) Mixing: mixing the cationic polymer solution and the anionic polymer solution and stirring for 10 minutes until flocs are generated, which is referred to as mixture A;
[0062] (4) The mixture A is centrifuged at a centrifugal force of 2000G for 15 minutes, and the supernatant is removed to obtain the product.
[0063] The concentration of the cationic polymer solution is 1 g / mL. The concentration of the anionic polymer solution is 1 g / mL.
[0064] In the step (3), the volume ratio of the cationic polymer solution to the anionic polymer solution is 1:1.
[0065] The second aspect of this embodiment provides a method for preparing the tissue filling composition, which comprises at least the following steps: adding cross-linked dextran microspheres to the polyelectrolyte gel and stirring evenly to obtain the tissue filling composition.
[0066] The third aspect of this embodiment provides a use of the tissue filling composition in the preparation of a biomaterial for treating stress urinary incontinence.
[0067] The preparation method of the biological material for treating stress urinary incontinence is as follows: the tissue filling composition is filled and sterilized by high-pressure steam to obtain the biological material.
[0068] Figure 2 This is a test diagram of the injectability of the polyelectrolyte gel produced during the preparation process of Example 1.
[0069] Figure 3 This is a graph showing the injectability test of the tissue filling composition prepared in Example 1.
[0070] Example 2
[0071] The specific implementation of this embodiment is the same as that of Embodiment 1, except that:
[0072] The concentration of the cationic polymer solution was 0.2 g / mL.
[0073] The pH value of the tissue filling composition is 6.75, and the swelling rate is 50.38%.
[0074] Example 3
[0075] The specific implementation of this embodiment is the same as that of Embodiment 1, except that:
[0076] The concentration of the cationic polymer solution was 0.5 g / mL.
[0077] The pH value of the tissue filling composition is 6.82, and the swelling rate is -22.35%.
[0078] Example 4
[0079] The specific implementation of this embodiment is the same as that of Embodiment 1, except that:
[0080] The concentration of the cationic polymer solution was 2 g / mL.
[0081] The pH value of the tissue filling composition is 6.62, and the swelling rate is 30.78%.
[0082] Example 5
[0083] The specific implementation of this embodiment is the same as that of Embodiment 1, except that:
[0084] The anionic polymer is sodium carboxymethyl cellulose.
[0085] The pH value of the tissue filling composition is 6.85, and the swelling rate is 18.67%.
[0086] Figure 1 This is a test chart of the swelling rate of the polyelectrolyte gel produced in the preparation process of Example 1-5 after accelerated aging at 60° C. for 10 days.
[0087] Performance Testing
[0088] 1. Polyelectrolyte gel test
[0089] Test method:
[0090] 1) Swelling rate test: Compare the swelling rate of the polyelectrolyte gel produced in the preparation process of Examples 1-5 after accelerated aging at 60°C for 10 days. Swelling rate calculation method: The initial mass of the gel is m o After swelling for 10 days, the gel mass is m1, and the calculation formula is 100%*(m1-m o ) / m o The test results are shown in Table 1 and Figure 1 .
[0091] When the tissue filling composition is used in the preparation of biological materials for treating stress urinary incontinence after filling and high-pressure steam sterilization, the urethra itself is narrow, and excessive swelling may lead to excessive filling pressure, causing discomfort to the human body, and seriously causing urethral swelling, affecting excretion. As can be seen from Table 1, the polyelectrolyte gel of the present application can be regulated within a lower swelling range (-50% to 50%), thereby avoiding the above problems. Figure 1 It can be seen that by comparing the morphology of the polyelectrolyte gel of the present application before and after accelerated aging at 60° C. for 10 days, it can be seen that the gel always maintains integrity and stability, and thus can achieve long-lasting and effective filling.
[0092] 2) Injectability test: The polyelectrolyte gel prepared in Example 1 was tested for injectability using a 26G injection needle. The test results are shown in Figure 2 .
[0093] like Figure 2 As shown, the polyelectrolyte gel prepared in the present application has injectability and high cohesion; compared with the prior art sodium hyaluronate gel, which needs to be homogenized before it can be injected, the polyelectrolyte gel of this patent can be injected without homogenization or granulation.
[0094] 3) In vitro cytotoxicity test:
[0095] Test object: polyelectrolyte gel produced during the preparation of Examples 1-5.
[0096] Test method: Tested in accordance with the reference standard GB / T 16886.5-2017. Four concentrations (100%, 75%, 50%, 25%) of test sample extract, blank, 100% negative control and positive control were prepared with MEM culture medium (containing 10% fetal bovine serum), extracted for 72 hours, and the extraction ratio was 0.2g:1mL. Under the conditions of 37C and 5% COz, semi-confluent monolayers of L-929 (NIH3T3) mouse fibroblasts were cultured on 96-well plates with the test sample extract, blank and the other two controls. After 24+2h, MTT colorimetric determination was performed, and the cell survival rate was calculated by reading on a microplate reader at 570nm and 650nm. The cell survival rate was calculated according to the following formula: Survival rate % = R / R o x100. Where R is the average optical density of the test group, positive control group, and negative control group; R o The average optical density of the blank group. Test results > 70% indicate passing.
[0097] The test results of the polyelectrolyte gels produced during the preparation of Examples 1-5 were all qualified.
[0098] 2. Test of injectability of tissue filling composition
[0099] Test object: sample prepared in Example 1.
[0100] Test method: After using a 23G needle to test the injectability of the composition, observe under a microscope whether the microspheres remain intact. Figure 3 .
[0101] like Figure 3 As shown, the tissue filling composition prepared by the present invention is injectable, and the microspheres will not be damaged during the injection process, and the microspheres maintain integrity.
[0102] Table 1
[0103]
Claims
1. A tissue filling composition, characterized in that: According to mass percentage, the preparation raw materials include 4-6% cross-linked dextran microspheres, 1-2% polyelectrolyte gel, and the balance is made up of water; the pH value of the tissue filling composition is 6-8, and the swelling rate is -50% to 50%.
2. The tissue filling composition according to claim 1, characterized in that: The raw materials for preparing the polyelectrolyte gel include cationic polymer, anionic polymer and water.
3. The tissue filling composition according to claim 2, characterized in that: The preparation method of the polyelectrolyte gel comprises the following steps: (1) preparing a cationic polymer solution: dissolving the cationic polymer in water, stirring until the cationic polymer is completely dissolved, and setting aside; (2) preparing anionic polymer solution: dissolving anionic polymer in water, stirring until the anionic polymer is completely dissolved, and setting aside; (3) mixing: mixing the cationic polymer solution and the anionic polymer solution and stirring until flocs are generated, which is referred to as mixture A; (4) The mixture A is centrifuged to remove the supernatant to obtain the product.
4. The tissue filling composition according to claim 2, characterized in that: The cationic polymer includes chitosan quaternary ammonium salt.
5. The tissue filling composition according to claim 2, characterized in that: The anionic polymer includes at least one of sodium hyaluronate and sodium carboxymethyl cellulose.
6. The tissue filling composition according to claim 3, characterized in that: In the step (3), the volume ratio of the cationic polymer solution to the anionic polymer solution is (0.5-2):
1.
7. The tissue filling composition according to claim 3, characterized in that: The concentration of the cationic polymer solution is 0.2-2 g / mL.
8. The tissue filling composition according to claim 3, characterized in that: The concentration of the anionic polymer solution is 0.2-1 g / mL.
9. A method for preparing the tissue filling composition according to any one of claims 1 to 8, characterized in that: The method at least comprises the following steps: adding cross-linked dextran microspheres into polyelectrolyte gel and stirring the mixture evenly to obtain the product.
10. A use of the tissue filling composition according to any one of claims 1 to 8, characterized in that: Used in the preparation of biomaterials for the treatment of stress urinary incontinence.
Citation Information
Patent Citations
High-quality cross-linked sodium hyaluronate gel and preparation method thereof
CN103923328A
Composition for treating vesico-ureteral reflux, stress urinary incontinence and fecal incontinence and preparation method thereof
CN108721206A